(untitled) (Pakistan Journal of Science, 2025)
The aim of this study was to examine the effect of mating ratio (male: female) and vitamin E -Selenium supplementation on egg production and egg weight of quail breeders. Total 720 Japanese quails of ten weeks of age with an average of 50% egg production were divided into four groups A, B, C and D having male: female mating ratio of 1:1, 1:2, 1:3 and 1:4 respectively. All the four groups were further sub-divided into vitamin E -Selenium supplemented (at the rate of 1ml/6 liters of drinking water) and control sub-groups. Each sub-group was further replicated three times with 30quails/replicate. Egg production was significantly (P<0.05) affected by mating ratio and vitamin E -Selenium supplementation. The egg production was highest (72 %) in ratio 1:4 while the least (52 %) in 1:1 ratio. The egg production with the supplementation of vitamin E -Selenium was highest (77 %) in ratio 1:4 while the least (52 %) in 1:1 ratio. Egg weight was significantly (P<0.05) affected by mating ratio but vitamin E -Selenium supplementation had no significant (P<0.05) effect on egg weight. The highest egg weight was (12.2g) for 1:3 mating group while least was (10.25gm) for 1:1 mating group.